2017
DOI: 10.1016/j.bjorl.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Airway reconstruction: review of an approach to the advanced-stage laryngotracheal stenosis

Abstract: The review of our approach to open airway repair/reconstruction showed its efficacy in advanced-stage laryngotracheal stenosis. Good knowledge of a variety of reconstructive techniques is important to achieve good results in a variety of age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 37 publications
1
28
0
6
Order By: Relevance
“…Airway stenosis most frequently occurs in the larynx or the proximal trachea, and diagnosis as well as location of stenosis can be determined by flexible laryngoscope . All subjects in the current study had only one location of stenosis, with a breakdown of 30% subglottic stenosis, 30% glottis stenosis, and 40% tracheal stenosis (Table ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Airway stenosis most frequently occurs in the larynx or the proximal trachea, and diagnosis as well as location of stenosis can be determined by flexible laryngoscope . All subjects in the current study had only one location of stenosis, with a breakdown of 30% subglottic stenosis, 30% glottis stenosis, and 40% tracheal stenosis (Table ).…”
Section: Discussionsupporting
confidence: 92%
“…Airway stenosis most frequently occurs in the larynx or the proximal trachea, and diagnosis as well as location of stenosis can be determined by flexible laryngoscope. 8 All subjects in the current study had only one location of stenosis, with a breakdown of 30% subglottic stenosis, 30% glottis stenosis, and 40% tracheal stenosis (Table I). McCaffrey 60 reported that subglottic stenosis accounted for about 46% of all cases of LTS, followed by both subglottic and glottic stenosis (19%) and both subglottic and tracheal stenosis (18%).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…2,[4][5][6] T y p i c a l l y , m a n a g e m e n t s t r a t e g i e s a r e determined by the severity of obstruction in the subglottic lumen; the Cotton-Myer grading system is the classification most commonly used to this end: grade 1, < 50 % obstruction; grade 2, 51-70 % obstruction; grade 3, 71-99 % obstruction; and grade 4, complete luminal obstruction. 2,7 In general, mild stenoses (grades 1 and 2) are managed without surgery. In the past, the most severe grades were treated with a tracheostomy or an open surgery.…”
Section: Introductionmentioning
confidence: 99%